RETRACTED: PENGEMBANGAN MODUL PROBLEM BASED LEARNING BERBASIS SOCIAL EMOTIONAL LEARNING MASALAH POKOK EKONOMI - Safira Mardiyatul Husna; Siti Rochani; Robiyatul Akmalia; Sri Suci Rahmadani; Tiwi Putri Lestari; Rachmad Hidayat; Safira Mardiyatul Husna; Siti Rochani; Robiyatul Akmalia; Sri Suci Rahmadani; Tiwi Putri Lestari (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2024)
This article was retracted at the author's request because it was submitted to two journals. The document and its content has been removed from Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, and reasonable effort should be made to remove all references to this article.